2014
DOI: 10.1161/strokeaha.114.005331
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Symptomatic Intracerebral Hemorrhage Versus Lacunar Disease in Patients With Longstanding Hypertension

Abstract: Background and Purpose Hypertension results in a spectrum of subcortical cerebrovascular disease. It is unclear why some individuals develop ischemia and others develop hemorrhage. Risk factors may differ for each population. We identify factors that predispose an individual to subcortical symptomatic intracerebral hemorrhage (sICH) compared with ischemia. Methods Demographic and laboratory data were prospectively collected for hypertensive patients presenting with ischemic stroke or sICH during an 8.5-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In line with the previous studies,[ 17 18 37 40 49 ] our study also disclosed that large cerebral infarction, AF, and HA are associated with increased risk of HT for AIS patients. It will appear massive cerebral edema and severe BBB damage when patients exist large infarction volume, which could accelerate microvascular injury, facilitate HT rate, and expand hemorrhage size after reperfusion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the previous studies,[ 17 18 37 40 49 ] our study also disclosed that large cerebral infarction, AF, and HA are associated with increased risk of HT for AIS patients. It will appear massive cerebral edema and severe BBB damage when patients exist large infarction volume, which could accelerate microvascular injury, facilitate HT rate, and expand hemorrhage size after reperfusion.…”
Section: Discussionsupporting
confidence: 92%
“…This results in the increased infarct growth, higher final infarct volume, and more frequent severe HT. [ 49 ] The upper of HT in HA patients may attributed to the absence of effect from albumin. Because albumin has been proved to be markedly neuroprotective in AIS and traumatic brain injury based on the theories of directly protecting both parenchymal and vascular elements of the brain, maintaining microvascular integrity, diminishing brain edema, inhibiting endothelial cell apoptosis, transporting fatty acids to the post-stroke brain, and exerting antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Renal failure has also been associated with inflammation that may damage the small vessels, leading to increased permeability of the blood brain barrier over time. 22 26 …”
Section: Discussionmentioning
confidence: 99%
“…Although a low rate of AF detection in TIAs has been reported [21], our results suggest a subgroup of patients (cortical symptoms without a major cause) that could benefit more from prolonged cardiac monitoring strategies. The second cause of diverse etiology in the SR was hemorrhagic stroke, which occurred more frequently in patients with TIA of SAD etiology; these entities have similar pathophysiological mechanisms [22]. The Secondary Prevention of Small Subcortical Strokes (SPS3) trial study, one of the main studies of patients with SAD, reported higher hemorrhagic risk in these patients and emphasized that control of hypertension is as important as antithrombotic treatment [23].…”
Section: Discussionmentioning
confidence: 99%